2021
DOI: 10.3389/fmed.2021.761372
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Dendritic Cell Homing in COVID-19

Abstract: The high mortality of COVID-19 is mostly attributed to acute respiratory distress syndrome (ARDS), whose histopathological correlate is diffuse alveolar damage (DAD). Furthermore, severe COVID-19 is often accompanied by a cytokine storm and a disrupted response of the adaptive immune system. Studies aiming to depict this dysregulation have mostly investigated the peripheral cell count as well as the functionality of immune cells. We investigated the impact of SARS-CoV-2 on antigen-presenting cells using multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…Other studies have also shown DC deficits, reduced potential for stimulating naïve CD4+ T cells, upregulation of proinflammatory markers, increased proliferative response and delayed regeneration in COVID‐19 patients 63 . Lung tissue autopsies of COVID‐19 patients revealed impaired DC maturation or homing, mDC accumulation, and decreased migration to lymph nodes leading to deficient T‐cell response 64 . Hence, DCs continue to be in focus for COVID‐19 research, 65–74 and clinical trials e.g.…”
Section: Transcriptomic Analysis Sheds New Insights On the Regulation...mentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies have also shown DC deficits, reduced potential for stimulating naïve CD4+ T cells, upregulation of proinflammatory markers, increased proliferative response and delayed regeneration in COVID‐19 patients 63 . Lung tissue autopsies of COVID‐19 patients revealed impaired DC maturation or homing, mDC accumulation, and decreased migration to lymph nodes leading to deficient T‐cell response 64 . Hence, DCs continue to be in focus for COVID‐19 research, 65–74 and clinical trials e.g.…”
Section: Transcriptomic Analysis Sheds New Insights On the Regulation...mentioning
confidence: 94%
“…63 Lung tissue autopsies of COVID-19 patients revealed impaired DC maturation or homing, mDC accumulation, and decreased migration to lymph nodes leading to deficient T-cell response. 64 Hence, DCs continue to be in focus for COVID-19 research, [65][66][67][68][69][70][71][72][73][74] and clinical trials e.g. NCT04685603, NCT04816760 and NCT04523246.…”
Section: Transcriptomic Analysis Sheds New Insights On the Regulation...mentioning
confidence: 99%
“…Ahadome et al (2016) showed that classical DC contributed to ocular mucosal fibrosis through the retinoic acid pathway in a model of allergic eye disease. Impaired DC maturation can lead to inadequate T-cell response and contribute to organ fibrosis as observed in COVID-19 patients (Borcherding et al, 2021). It has been reported that DCs contribute to scar formation in liver fibrosis and multiple sclerosis directly through secreting metalloproteinase and their inhibitors (Rahman and Aloman, 2013).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…However, COVID-19 infection is characterized by lymphopenia ( 37 ). Probably, SARS-CoV-2 exerts immune evasion through impaired maturation of dendritic cells, leading to hampered dendritic cells (DCs) homing to lymph nodes and failure of T lymphocytes activation ( 38 ).…”
Section: Immunity and Inflammationmentioning
confidence: 99%